EFFECT OF BROKEN HOME ON EDUCATIONAL ACHIEVEMENTS OF PUPILS AT BASIC SCHOOLS LEVEL IN ADAMAWA STATE-NIGERIA - Garba, Ahmad; Iskandi, Iskandi; Adam, Safiya Abubakar (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research titled effect of broken home on the educational achievements of pupils in primary schools in Adamawa State-Nigeria, has focus on some selected basic schools, where 150 pupils were selected randomly, questionnaire was used as the research instrument for data collection, and data collected were analyzed using descriptive statistics. Specifically, Pearson Product-Moment Correlation Statistics, it was used to compute and analyze the mean and standard deviation of the percentage of the responses from the respondents, based on the research findings, it was discovered that broken homes affect the pupils’ education psychologically, economically, emotionally, and academically. therefore, results from the findings show the level of pupils' academic performance in Adamawa State, Also the results of the findings showed some elements of parental status which include education level, income level, motivation level and marital status affect pupils' academic performance, Furthermore, the study has shown that parental background has significant relationship with pupils in primary schools and their academic performance in the state, and the study recommended that; to avoid broken home the society should put an eye on the couples from broken home as this Will help to minimized people from allowing their homes get broken, as well as tolerance and forgiveness among couples should be encouraged so as to allow peace to exist in their homes.